Systemic Violence and High Stakes Testing - Ivan E. Watts (Educational Considerations, 2003)
The use of high stakes testing as the primary tool of school reform is sweeping the nation. Proponents of standardized tests, including most state legislatures, the President, governors, boards of education and even the American Federation of Teachers, have embraced the rhetoric of higher and tougher standards.